International Security and Challenges Along "One Belt, One Road" in Central Asia - Dmytro Burtsev (Vasyl Stefanyk Precarpathian National University, 2022)
The concept of international security has numerous dimensions and interpretations, because of a wide scope of threats and challenges, which have various roots and reasons and depend on the region of the development of a particular security issue. This accounts for the choice of the form: the best way to discuss international security is to use particular cases while conducting the research. This method allows us to perceive the issue as a complex notion in particular circumstances while avoiding unnecessary generalization of the researched object. Current research is devoted to the issue of security assets in Central Asian republics (Kazakhstan, Uzbekistan, Turkmenistan, Tajikistan, and Kirgizstan). Moreover, the research does not only take into consideration security threats purely as a notion but also brings in another variable to the discussion: a factor of the Chinese "One Belt, One Road" initiative. This fact allows the research to obtain geopolitical meaning and depth. For China realization of the OBOR initiative means far more than the creation of a mechanism of international logistics, investments, and cooperation. Using the OBOR China tries to promote a scale of values, which is different from the Western one. Moreover, building the OBOR grants China the role of an international superpower as well as a new pole of gravity in international relations. The research also addresses the question of the importance of Central Asia as a geopolitical bridge. The control over it has been a debatable issue among international players since the early 19th century, and it still has not lost its importance because the region has its borders close to the borders of the Russian Federation from the south and China from the west. Central Asia is also a region with numerous internal problems: on one hand, they are very similar for all the five republics of the region, but, on the other hand, they have their peculiarities differing from country to country. First of all, these concerns are related to the newly emerged unconventional security threat like religious radicalism and extremism: particular features of this phenomenon are different from country to country, and it does not have a unified solution. The last fact endangers not only national states of the region, but also countries of the neighboring region of Central Asia. In general, the research discusses the correlation of the OBOR as an international phenomenon with possible security risks for this project in the region of Central Asia.